Proteomic analysis of exosome-enriched fractions derived from cerebrospinal fluid of amyotrophic lateral sclerosis patients. (November 2020) - Hayashi, Noriko; Doi, Hiroshi; Kurata, Yoichi; Kagawa, Hiroyuki; Atobe, Yoshitoshi; Funakoshi, Kengo; Tada, Mikiko; Katsumoto, Atsuko; Tanaka, Kenichi; Kunii, Misako; Nakamura, Haruko; Takahashi, Keita; et al.
Highlights: Proteomic analysis was performed on exosome-enriched fractions from CSF of ALS. Exosome-enriched fractions of CSF revealed increased level of NIR in ALS. NIR was pathologically reduced in the nucleus of ALS motor neurons. Abstract: Exosomes contain many proteins associated with neurodegenerative diseases. To identify new candidate biomarkers and proteins associated with amyotrophic lateral sclerosis (ALS), we performed liquid chromatography-tandem mass spectrometry proteomic analysis of exosome-enriched fractions isolated from cerebrospinal fluid (CSF) of sporadic ALS patients using gel filtration chromatography. Proteomic data revealed that three proteins were increased and 11 proteins were decreased in ALS patients. The protein with the greatest increase in exosome-enriched fractions of CSF derived from ALS was novel INHAT repressor (NIR), which is closely associated with nucleolar function. By immunohistochemical analysis, we found that NIR was reduced in the nucleus of motor neurons in ALS patients. Our results demonstrate the potential utility of our methodology for proteomic analysis of CSF exosomes and suggest that nucleolar stress might play a role in sporadic ALS pathogenesis through the dysfunction of NIR.